The reliability of a 30-minute performance test on a Lode cycle ergometer - Driller, M. W. (Journal of Science and Cycling, 2012)
High retest reliability is desirable in tests used to monitor athletic performance. The purpose of the present study was to determine the reliability of a 30-minute cycle test on a cycle ergometer (Lode, Groningen, Netherlands). Following an incremental VO2max test, 10 highly-trained cyclists (mean ± SD; age = 30 ± 6 years; VO2max = 67.7 ± 2.5 mL.kg-1.min-1) completed three 30-minute cycling tests on a Lode cycle ergometer each separated by more than 48 hours. The cycle test implemented a fixed workload for 15-minutes (set at 70% VO2max power output), followed by a 15-minute time-trial. Variables determined during the test were mean power (Wmean), blood lactate concentration at 15-minutes (BL15), peak blood lactate concentration (BLpeak) and mean heart rate (HRmean). Wmean in trial 1 (312?± 23 W) increased by 0.8% (95% confidence interval: -0.7 to 2.3%) in trial 2 and by a further 0.4% (-0.3 to 1.1%) in trial 3. The typical error of measurement expressed as a coefficient of variation (CV%) for Wmean was 1.3% (1.0 to 1.8%). The CV for BL15 was 10.9% (8.3 to 15.9%), BLpeak; 8.4% (6.5 to 13.0%) and HRmean; 2.4% (1.8 to 3.4%). The average intraclass correlations between trials were Wmean: 0.98 (0.96 to 1.00), BL15: 0.94 (0.85 to 0.98), BLpeak: 0.88 (0.71- 0.97) and HRmean: 0.88 (0.71 to 0.97). A strong correlation existed between VO2max and PPO in the incremental test and Wmean in the 30-minute TT (r = 0.86, 0.93, respectively). The testing protocol performed on a Lode cycle ergometer in the current study is reproducible in highly-trained cyclists, making it a reliable method for monitoring cycling performance.